1999
DOI: 10.1115/1.2818497
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Diffusion Behaviors for Interface Between Ni-Based Super Alloys and Vacuum Plasma Sprayed MCrAlY Coatings

Abstract: The object of this study is overlay coatings of MCrAlY alloy sprayed by a vacuum plasma spray (VPS) process for the protection against high-temperature corrosion and oxidation in the field of gas turbine components. Reaction diffusion behaviors at the interface between the MCrAlY coatings and the substrate, which have an important effect on coating degradation, have not always been clarified. Three kinds of substrate, equiaxis 1N738LC, directional solidified CM247LC and single-crystal CMSX-2, and the four kind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 15 publications
3
16
0
Order By: Relevance
“…The interdiffusion of the alloying elements drives the microstructure changes [9]. Itoh et al's research [8] indicated that the microstructures in the substrate were mainly controlled by the diffusion of Co (and Ni) through the CSI, which agrees with the results in this work. The microstructures in the GPDZ are different when the substrate is coated with different coatings (Fig.…”
Section: Microstructural Evolution Near Csisupporting
confidence: 82%
See 4 more Smart Citations
“…The interdiffusion of the alloying elements drives the microstructure changes [9]. Itoh et al's research [8] indicated that the microstructures in the substrate were mainly controlled by the diffusion of Co (and Ni) through the CSI, which agrees with the results in this work. The microstructures in the GPDZ are different when the substrate is coated with different coatings (Fig.…”
Section: Microstructural Evolution Near Csisupporting
confidence: 82%
“…For instance, due to the diffusion of Co into the substrate, secondary β phase (SBP) may form in the substrate [8]. Taylor et al's result [10] further showed that the Al in the SBP could diffuse back to the coating and be used for the oxidation at the coating surface.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations